CALCULATION OF LOSSES FOR DAMAGE TO WARRANTY HOUSES IN MEUGAH PROPERTY HOUSING: STUDY ACCORDING TO THE SALE AND PURCHASE CONTRACT - Mahera, Rauza; Akbar, Hajarul (JURISTA: Jurnal Hukum dan Keadilan, 2024)
The warranty agreement is intended as an effort to protect consumers or buyers from various possible damage to the house sold by the developer or the poor quality of the house being transacted. In the warranty agreement, the developer and its consumers include several standard agreement clauses that contain several things so that consumers can claim the quality of the house they bought. This type of research is a qualitative descriptive approach through case studies. In this study shows that the warranty system applied by the developer uses an oral agreement, not set forth in writing, the developer provides a warranty to its consumers only for 3-6 months the house that has been purchased by the consumer is no longer available to repair damage to the house, but in one transaction the house has a lot of physical damage so that the buyer must deal with the developer again, in this case the developer also felt disadvantaged because the builders were original in building the house so that after the house was completed there was damage to the house, the conclusion explains that in this problem it is necessary when buying and selling transactions to also use khiyar conditions in it, this is useful for circumstances at any time the qualifications of the house and the agreement are not the same as at the beginning promised and the buyer can cancel the agreement, because it is only limited to verbal agreements, the agreement that has been agreed upon at the beginning results in legal weaknesses and losses between the two parties.